The influence of social capital on college students’ academic adaptation: the mediating role of positive emotional experience - Tong, Qingquan; Cheng, Jianshan; Yang, Yanxuan (Frontiers in Psychology, 2025)
IntroductionThis study aims to examine the impact of social capital on college students’ academic adaptation and to explore the underlying mechanism—specifically, the mediating role of positive emotional experience. By integrating perspectives from social capital theory and positive psychology, it seeks to enrich theoretical understandings of higher-education adaptation.MethodsA total of 428 undergraduates from a comprehensive university participated in this study. Data were gathered using a self-developed Social Capital Scale, an Academic Adaptation Scale, and a Positive Emotional Experience Scale. Descriptive statistics and confirmatory factor analysis were conducted in SPSS 26.0 and AMOS 24.0, respectively. Structural equation modeling was used to test the hypothesized paths, and the mediating effect of positive emotional experience was assessed via Hayes’s PROCESS macro (Model 4) with 5,000 bootstrap samples.ResultsSocial capital had a significant direct predictive effect on academic adaptation (β = 0.251, p < 0.001). The path from social capital to positive emotional experience was also significant (β = 0.679, p < 0.001), as was the path from positive emotional experience to academic adaptation (β = 0.583, p < 0.001). Bootstrap analysis indicated an indirect effect of 0.396 (95% CI [0.283, 0.523]), excluding zero, demonstrating that positive emotional experience partially mediates the relationship between social capital and academic adaptation.DiscussionThese findings support social capital theory and broaden-and-build theory, revealing a synergistic mechanism whereby external social support resources enhance students’ positive emotional experiences, which in turn promote academic adaptation. Practically, universities should foster strong teacher–student and peer support networks while implementing interventions to cultivate positive emotions, thereby leveraging both pathways to improve students’ adaptation to academic life.